Knowledge and attitude towards pain relief in labor among final year midwifery students: A cross-sectional study. (2020) - Endalew, Nigussie Simeneh; Tawuye, Hailu Yimer; Melesse, Debas Yaregal
Abstract: Background: Poor attitudes and lack of knowledge about labor pain has long been demonstrated to burden the health professionals, as well as the women. In developing countries, labor analgesia practice is not well established and undermined. Therefore, the aim of this study was to explore final year midwifery students' knowledge and attitudes towards pain relief during labor. Methods: A cross-sectional study was conducted among final year undergraduate midwifery students using structured, and self-administered questionnaire (N = 130). Descriptive statistics were performed. Results were presented using narrations, means and standard deviations, percentage, figure and tables. Univariate analysis was used to assess the association between demographic variables with poor knowledge and attitudes. Results: of 130 students participated, the majority, 88% of respondents understood that women can feel moderate to severe pain during labor. However, only less than half of the participants had knowledge of labor pain should be relieved. The majority, 70% of students did not have awareness about the methods of labor analgesia. Conclusions: Although the majority of final year midwifery students were agreed with women can feel moderate to severe labor pain, almost more than half of the students were not aware of the painless labor in the hospital. Most of the students believed that pharmacological methods of labor analgesia will affect the labor, baby, and mother. Therefore, considerable attention in preservice teaching and training about labor pain and analgesia for midwifery students is recommended. Highlights: 88% of respondents understood that women can feel moderate to severe pain during labour. The majority, 70% of students did not have awareness about the methods of labour analgesia. Almost more than half of the students were not aware of the painless labour in hospital. Considerable attention in preservice teaching and training about labour pain and analgesia for midwifery students.